Implementation of the Talaqqi Method Tahsin Program in Eradicating Al-Qur'an Illiteracy at SMP N 2 Limboto Barat - Dharma Lauma; Najamuddin Petta Solong (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
The problem of Koran illiteracy is still a challenge among Muslim students, including at SMP N 2 Limboto Barat. This research aims to evaluate the effectiveness of the tahsin program using the talaqqi method in eradicating Al-Qur'an illiteracy in the school. The research method used is a mixture of qualitative and quantitative approaches. Data was collected through observation, interviews, and Al-Qur'an reading ability tests before and after the program was implemented. The research results showed a significant increase in students' ability to read the Al-Qur'an, especially in the aspects of tajwid, makhraj letters, and reading fluency. The talaqqi method, which emphasizes direct learning with teacher guidance, has proven effective in helping students improve their reading of the Qur'an. Even though there are obstacles such as limited time and number of teachers, the solution implemented is in the form of additional class sessions and the involvement of more competent teachers and alumni. In conclusion, the tahsin program using the talaqqi method at SMP N 2 Limboto Barat is effective in improving students' Al-Qur'an reading skills, so it can be recommended for implementation in other schools to overcome the problem of Al-Qur'an illiteracy.